Association between HDL-C and chronic pain: data from the NHANES database 2003–2004 - Mi, Panpan; Dong, Haoran; Chen, Shengle; Gao, Xuan; Cao, Xu; Liu, Yong; Wang, Huijie; Fan, Guofeng (Frontiers in Medicine, 2024)
Objective: High-density lipoprotein cholesterol (HDL-C) has been reported to be associated with pain symptoms of various diseases, and its anti-inflammatory and antioxidant mediation is related to the pathogenesis of chronic pain. This study aims to evaluate the relationship between HDL-C levels and chronic pain in American adults.This cross-sectional study used data from American adults aged 20 and above during the 2003-2004 National Health and Nutrition Examination Survey (NHANES) cycle. Participants were divided into 4 groups based on HDL-C quartiles. We used chi-square tests and Student's t-tests or Mann-Whitney U tests to analyze categorical variables and continuous variables to compare differences between groups. Multivariate logistic regression analysis was used to study the association between HDL-C levels and the risk of chronic pain. Likelihood ratio tests were used to assess interactions between subgroups, and sensitivity analyses were conducted.Results: Our final analysis included 4,688 participants, of which 733 (16.4%) had chronic pain. In the multivariate logistic regression model adjusted for covariates, there was a negative correlation between HDL-C levels and chronic pain. Specifically, for every 20 unit increase in HDL-C, the risk of chronic pain decreased by 26%. Compared with the lowest HDL-C quartile (< 43 mg/dL), the highest HDL-C quartile (≥ 64 mg/dL) was associated with a 24% reduction in the risk of chronic pain.No interaction factors affecting the relationship between HDL-C and chronic pain were found in the subgroup analysis.Conclusions: This study demonstrates a negative association between HDL-C levels and chronic pain in US adults, providing insights into the pathogenesis of chronic pain and potential improvements in chronic pain management strategies.